Patterns of dietary supplement use among older men and women in the UK: findings from the Hertfordshire Cohort Study. - Denison, H; Jameson, K; Syddall, H; Dennison, E; Cooper, C; Sayer, A; Robinson, S (2012)
OBJECTIVES: To determine patterns of supplement use in a UK community-dwelling older population, and to investigate the extent to which supplement user groups differ, in terms of their sociodemographic and lifestyle characteristics, diet and morbidity. DESIGN: Cross-sectional cohort study. SETTING: Home interview and clinic visit. PARTICIPANTS: 3217 Hertfordshire Cohort Study participants, aged 59 to 73. MEASUREMENTS: Information was obtained on the participant's social and medical history by a trained research nurse. Diet over the preceding 3 months was assessed by Food Frequency Questionnaire; compliance with 'healthy' eating recommendations was defined using individual scores for a 'prudent' dietary pattern, identified using principal components analysis. Details of all dietary supplements taken in the preceding 3 months were recorded. Individual supplements were allocated to one of 10 types based on their nutrient composition. Cluster analysis was used to define groups of supplement users. RESULTS: 45.4% of men and 57.5% of women reported taking at least one dietary supplement in the previous 3 month period. There were 5 distinct clusters of supplement users; these were common to men and women. They were labelled according to the principal supplement taken; oils, glucosamine, single vitamins, vitamins and minerals, and herbal products. These groups differed in their social class and prudent diet score, but few other characteristics. With the exception of a difference in diagnosis of diabetes among the women, there were no differences in morbidity between the supplement groups in either men or women. CONCLUSIONS: Dietary supplement use is high in this population. There are distinct patterns of supplement use, which are related to sociodemographic and lifestyle characteristics including diet, though there were few clear differences in morbidity.